Ekofeminisme dan Perjuangan Perempuan Melawan Eksploitasi Lingkungan di Pulau Sangihe - Afandi, Iswan; Juanda, Juanda (Universitas Lampung, 2025)
This study aims to analyze and describe the relationship between women and nature in the novel Perempuan yang Menunggu di Lorong Menuju Laut by Dian Purnomo. The theory used in this study is Vandana Shiva's ecofeminism theory, which highlights the relationship between the exploitation of nature and the oppression of women and how women have an important role in maintaining ecological balance. This study uses a qualitative method. The content analysis technique was used in this study. The study's results, namely: a) the role of women in protecting nature (environmental justice), obtained a dominant percentage of 10.72%. This confirms that the struggle of women in this novel focuses on ecological protection as a form of resistance to the exploitation of natural resources in Sangihe; b) local knowledge data 5.51% shows how cultural heritage and community wisdom play an important role in efforts to protect the environment; c) natural condition data 2.83% reflects the real impact of exploitation on the ecosystem and life of the Sangihe Community; d) data on the relationship between women and nature 2.12% confirms the close relationship between environmental sustainability and the role of women as guardians of ecological balance; and e) data on feminine values in maintaining the balance between women and nature 1.73%. This illustrates how caring, sustainability, and harmony contribute to environmental protection. The findings demonstrate the close relationship between women and nature that reflects the values of environmental feminism, especially environmental justice and the role of women in maintaining ecological balance. The contribution of this study is to strengthen the understanding of the importance of women's roles in environmental issues and ecofeminism in Indonesia, as well as its relevance in the context of environmental policies and social movements.Keywords: Ecofeminism, Sangihe Women, Mining, Environmental Exploitation